2006
DOI: 10.1111/j.1365-3059.2006.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of nonhost plants in managing Plasmodiophora brassicae

Abstract: Germination of resting spores of Plasmodiophora brassicae , causal agent of clubroot in crucifers, may be stimulated by certain nonhost plants. Without a host plant to infect, such germination would lead to a reduced persistence of resting spores in the soil. The effect of four nonhost plants on P. brassicae was investigated in a 3-year field experiment and a 14-month glasshouse experiment. Three of the plant species used, leek ( Allium porrum ), winter rye ( Secale cereale ) and perennial ryegrass ( Lolium pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…A crop that stimulates germination of resting spores of P. brassicae was grown as a bait crop to stimulate resting spore germination, and then ploughed down before the pathogen completed its life cycle, thus reducing the inoculum load in the field. However, the results of empirical studies to assess the efficacy of this approach were inconsistent (Friberg et al, 2006). Use of bait crops to stimulate germination of resting spores did not reduce clubroot incidence or severity in northern Europe (Friberg et al, 2005(Friberg et al, , 2006, but a 5-year fallow period resulted in a substantial decrease in resting spore populations compared with continuous cultivation of a clubroot-resistant Japanese radish (Raphanus sativus var.…”
Section: Baiting Cropsmentioning
confidence: 98%
See 3 more Smart Citations
“…A crop that stimulates germination of resting spores of P. brassicae was grown as a bait crop to stimulate resting spore germination, and then ploughed down before the pathogen completed its life cycle, thus reducing the inoculum load in the field. However, the results of empirical studies to assess the efficacy of this approach were inconsistent (Friberg et al, 2006). Use of bait crops to stimulate germination of resting spores did not reduce clubroot incidence or severity in northern Europe (Friberg et al, 2005(Friberg et al, , 2006, but a 5-year fallow period resulted in a substantial decrease in resting spore populations compared with continuous cultivation of a clubroot-resistant Japanese radish (Raphanus sativus var.…”
Section: Baiting Cropsmentioning
confidence: 98%
“…Resting spore germination is stimulated by proximity to the roots of both host and non-host plants (Friberg et al, 2006). This appears to be a general response to root exudates, because the root exudates of several non-hosts such as perennial ryegrass, leeks (Allium ampeloprasum var.…”
Section: Baiting Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the glasshouse experiment, there was a reduction in disease incidence in all plant treatments, compared with plant-free controls, following incorporation and decomposition of plant roots. The results indicated that use of nonhost plant species for reducing club root disease incidence would not be an effective approach (Friberg et al 2006 ) . On the other hand, intercropping fi eld vegetables with other crops has been shown to have potential to be used as alternative to the application of chemicals for reducing the disease incidence.…”
Section: Multiple Croppingmentioning
confidence: 96%